Pemeriksaan IVA Langkah Bijak Deteksi Dini Kesehatan Wanita - Suryaningsih, Eny; Atiqahrana, Riqqah; Wahyuningsih, Beti; Yusni, Yusni; Fadillah, Ria Nur; Putri, Yesi (Jurnal Gotong Royong, 2026)
IVA examination (Visual Acetic Acid Inspection) is an effective and simple method of early detection of cervical cancer. This wise step allows women to check their reproductive health independently and regularly, so they can recognize abnormal changes early. By using affordable ingredients and a fast process, IVA has become the main choice in women's health programs in Indonesia. Early detection through this examination is very important to increase the chances of treatment and saving lives. Through preventive awareness, women can maintain their health with smart and responsible steps.